A Mean-Variance Analysis of United States Long-Term Portfolio Foreign Investment - Miller, Norman C.; v. N. Whitman, Marina (Quarterly Journal of Economics, 1970)
I. Introduction, 175. — II. The basic model, 177. — III. Empirical specification, 179. — IV. Empirical estimation, 187. — V. Poliep' implications, 193.— Appendix: Symbols, definitions, and data sources, 195.